Major depression prevalence among Syrian migrants seeking asylum in Greece: a cross-sectional survey. (March 2018) - Poole, Danielle; Hedt-Gauthier, Bethany; Raymond, Nathaniel; Bärnighausen, Till
Abstract: Background: Since the start of the Syrian war in 2011, 250 000 Syrians have sought asylum in Greece, and more than 1 million people have attempted to reach other countries in the European Union by travel through Greece. Migrants face a myriad of poor mental health outcomes, including major depression requiring treatment. However, the prevalence of major depression among Syrians undergoing the asylum process—a potential window for intervention—has not been reported. This study quantified the prevalence of major depression among Syrian migrants in a refugee camp setting. Methods: We did a cross-sectional survey via face-to-face interviews in a Syrian refugee camp in Greece from January 16–31, 2017. Individuals aged 18 years or older, residing in the refugee camp, and with verbal Arabic or English language skills were eligible to participate. The Patient Health Questionnaire-8 (PHQ-8) was used to evaluate depression. Sociodemographic and displacement data were collected using a standardised instrument. The study was approved by the Harvard T H Chan School of Public Health (Protocol IRB16-2015) and all participants provided oral informed consent. Findings: 135 surveys were completed, with a response rate of 97%, representing 38% of the adult population in the refugee camp. The mean age of participants was 31·4 years (range 18–61 years); 40·7% of the sample was female; 74·4% of the participants had ever married; and 67·2% had children. 33·4% of participants had not attended secondary school, including 11·4% who had never attended school. The median time spent in the asylum process in Greece was 10 months (<1–49 months). Major depression was detected in 43·7% (95% CI 37·2–50·4) of participants. 20·7% of participants reported no symptoms of depression, and 35·6% were found to have mild depression. Interpretation: Syrian migrants face an extraordinarily high burden of major depression as they seek asylum. The high prevalence of major depression may be explained by the particular plight of fleeing the Syrian war, the social and physical conditions in the refugee camp, as well as the protracted asylum process—a period extending beyond 1 year in Greece since the adoption of the EU–Turkey Statement. The incorporation of screening and treatment into service provision within refugee camps is urgently needed, particularly in the context of delayed asylum procedures. Funding: International Data Responsibility Group.